Questioning Organizational Legitimacy: The Case of U.S. Expatriates - Johnson, Jackie (Journal of business ethics, 2003)
It has been estimated that U.S. companies with global business operations can reduce their U.S. tax bill by up to 10 percentage points if they reincorporate in a zero or low tax offshore jurisdiction. But this activity, at a time of national crisis following the September 11 terrorists' attacks and recent spate of corporate scandals, has received a less than sympathetic response from the U.S. media, ordinary taxpayers, shareholders and politicians as concerns are raised about the reduction of the tax base and the lack of oversight and regulation in offshore centres. Offshore reincorporation has been condemned as immoral, unconscionable, dishonest and unpatriotic, accusations that cast doubt on the legitimacy of the companies concerned. In question is their right to conduct business in the U.S. and in particular, their right to still be viewed as American. Their legitimacy once bestowed so readily by the company's shareholders is now being questioned not only by shareholders but also the media, politicians, government regulators, pension funds and labour unions. Expatriate companies have been slow to respond to questions of their legitimacy, viewing their offshore move as a financial decision needing only the consent of their shareholders. However, times have changed and corporate legitimacy is now in the hands of all the company's stakeholders. Companies will need to explicitly consider the determinants of their legitimacy and the implications of the implied social contract under which they operate, to remain relevant in the days ahead.